A Discrete Fourier Transform Based Dithering Signal Generation Method for Reduced Quantization Error - Ye, Chang-Qing; Xiong, Xing-Zhong (Journal of Vibration Testing and System Dynamics, 2026)
Addressing the impact of quantization error in analog-to-digital converter (ADC) for signal processing, a Discrete Fourier Transform (DFT) based method for the generation of dithering signals is presented. Eﬀective in reducing quantization error, the dithering signal generated using the method is not only independent of the input signal but also can improve the performance of the ADC. To illustrate the advantages of the dithering signal reconstructed using the method, three kinds of typical dithering eﬀects, namely, Triangular Distribution Dithering, Gaussian Distribution Dithering and Uniform Distribution Dithering on the quantization error in an ADC are considered. The properties of three practical dithering signals are investigated. It is shown that while these typical dithering may be useful they are some potential problems. The dithering signals reconstructed using the DFT based generation scheme is shown to contribute signiﬁcantly to reducing quantization error. Numerical experiments and theoretical analyses demonstrate that the DFT based dithering reconstruction can obtain prominent performance for ADC in comparison to typical dithering signals.